If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + -10k = 0 Reorder the terms: -10k + -4x = 0 Solving -10k + -4x = 0 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '4x' to each side of the equation. -10k + -4x + 4x = 0 + 4x Combine like terms: -4x + 4x = 0 -10k + 0 = 0 + 4x -10k = 0 + 4x Remove the zero: -10k = 4x Divide each side by '-10'. k = -0.4x Simplifying k = -0.4x
| 3(x+2.94)=2x | | 75x^2=3 | | 2m+7-2m+6=x | | 5x+9.16=3x+12 | | 12(3x+6)-7(2x-4)=4x-20 | | 15x-35=8 | | 5x+7=12x-56 | | 32=5x-3 | | -x^4=25-26x^2 | | 15+4a=7a | | -3.8x+1.2=-17.8 | | 35-8=x | | 9x^2-2=o | | n+2=-14-na | | (1+2)+0= | | 3x=5x+70 | | 3-1.5(x+1)=6x-9 | | 63x^3+11x^2=-36x | | 20+1.25n=2.50n | | 121=100+0.3x | | -8x-3+9x=-9x+3 | | 6(b-a)=2(4a-3b) | | 8x+10=6x+90 | | 205+205+205= | | 0=-16x^2+96x+640 | | 4(x+1)-5(3-x)=14x-2(5x-3) | | 7-4(s-3)=23 | | .5x+3x+(2x+4)= | | 5=-16t^2+45t+6 | | 12x-108=-4x+36 | | 3x=2(-3)-18 | | 5u^2=-26u-5 |